Interlayer exciton-polaron effect in transition metal dichalcogenides van der Waals heterostructures. (November 2019) - Dong, Xi-Ying; Li, Run-Ze; Deng, Jia-Pei; Wang, Zi-Wu
Abstract: Interlayer exciton-polaron is formed arising from the exciton-surface optical (SO) phonons coupling in transition metal dichalcogenides (TMDS) van der Waals heterostructures, in which SO phonons are induced by the inserted hexagonal boron nitride (h-BN) and the coupling effect is evaluated by means of two unitary transformations. We find that the binding energy of interlayer exciton decreases obviously due to this exciton-polaron effect. The binding energy can be tuned by the numbers of inserted h-BN layers and the interlayer distance between two TMDS layers. Moreover, the critical temperature of quantum Bose gases composing of these interlayer excitons increases in a large scale due to the variations of binding energy. These theoretical results provide possible channels to adjust the properties of interlayer excitons in two-dimensional van der Waals heterostructures.